2003
DOI: 10.1097/00000478-200304000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Zone B-Cell Lymphoma in Children and Young Adults

Abstract: We describe the clinicopathologic findings of 48 cases of marginal zone B-cell lymphoma (MZL) in children and young adults, a disease that has been recognized previously only rarely in this age group. Patients ranged in age from 2 to 29 years, with pediatric patients (< or =18 years) comprising 52% of the cases. As in adults, both primary nodal (N) and extranodal (E) MZL were observed. However, primary NMZL comprised the majority of the cases (67%) and demonstrated distinctive clinical and histologic features.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 26 publications
10
158
1
2
Order By: Relevance
“…Similarly to pediatric FL, NMZLs in children show a striking male predominance, present as localized disease, and are relatively well controlled with only local therapies. 86,87 The biologic characteristics are not well known, but recent genetic studies have shown similar chromosomal aberrations as in the adult counterparts (trisomies 3 and 18 and occasional IGH@ and MALT1 rearrangement) but at lower frequency. 88 Florid follicular and marginal zone hyperplasias that occur in children further complicate the diagnosis of pediatric FL and MZL; these cases occasionally have monotypic expression of immunoglobulin light chains, and in some cases evidence of clonality of IG genes at the molecular level.…”
Section: Clinical Features In Disease Definitionmentioning
confidence: 99%
“…Similarly to pediatric FL, NMZLs in children show a striking male predominance, present as localized disease, and are relatively well controlled with only local therapies. 86,87 The biologic characteristics are not well known, but recent genetic studies have shown similar chromosomal aberrations as in the adult counterparts (trisomies 3 and 18 and occasional IGH@ and MALT1 rearrangement) but at lower frequency. 88 Florid follicular and marginal zone hyperplasias that occur in children further complicate the diagnosis of pediatric FL and MZL; these cases occasionally have monotypic expression of immunoglobulin light chains, and in some cases evidence of clonality of IG genes at the molecular level.…”
Section: Clinical Features In Disease Definitionmentioning
confidence: 99%
“…Similar to PTFL, pediatric NMZL is more common in males, especially in patients under 18 years of age, with a M:F ratio of 20:1. 67 It presents as asymptomatic isolated lymphadenopathy, commonly in the head and neck region. Morphologically, residual follicles are often present, and show fragmentation with thin mantle zones ( Figure 2E-I).…”
Section: Pediatric Variant Of Nodal Marginal Zone Lymphomamentioning
confidence: 99%
“…96 Characteristic features were a striking male predominance and an indolent disease course. In contrast to NMZL in adults, pediatric NMZLs presented with only localized disease, corresponding with an excellent prognosis.…”
Section: Pediatric Nodal Marginal Zone Lymphomamentioning
confidence: 99%